Metabolomics analysis identifies sex-associated metabotypes of oxidative stress and the autotaxin–lysoPA axis in COPD. Issue 6 (22nd June 2017) - Naz, Shama; Kolmert, Johan; Yang, Mingxing; Reinke, Stacey N.; Kamleh, Muhammad Anas; Snowden, Stuart; Heyder, Tina; Levänen, Bettina; Erle, David J.; Sköld, C. Magnus; Wheelock, Åsa M.; Wheelock, Craig E.
Chronic obstructive pulmonary disease (COPD) is a heterogeneous disease and a leading cause of mortality and morbidity worldwide. The aim of this study was to investigate the sex dependency of circulating metabolic profiles in COPD. Serum from healthy never-smokers (healthy), smokers with normal lung function (smokers), and smokers with COPD (COPD; Global Initiative for Chronic Obstructive Lung Disease stages I–II/A–B) from the Karolinska COSMIC cohort (n=116) was analysed using our nontargeted liquid chromatography–high resolution mass spectrometry metabolomics platform. Pathway analyses revealed that several altered metabolites are involved in oxidative stress. Supervised multivariate modelling showed significant classification of smokers from COPD (p=2.8×10 −7 ). Sex stratification indicated that the separation was driven by females (p=2.4×10 −7 ) relative to males (p=4.0×10 −4 ). Significantly altered metabolites were confirmed quantitatively using targeted metabolomics. Multivariate modelling of targeted metabolomics data confirmed enhanced metabolic dysregulation in females with COPD (p=3.0×10 −3 ) relative to males (p=0.10). The autotaxin products lysoPA (16:0) and lysoPA (18:2) correlated with lung function (forced expiratory volume in 1 s) in males with COPD (r=0.86; p<0.0001), but not females (r=0.44; p=0.15), potentially related to observed dysregulation of the miR-29 family in the lung. These findings highlight the role of oxidative stress in COPD, and suggest that sex-enhanced dysregulation in oxidative stress, and potentially the autotaxin–lysoPA axis, are associated with disease mechanisms and/or prevalence. Oxidative stress and the autotaxin–lysoPA axis evidence sex-associated metabotypes in the serum of COPD patients http://ow.ly/kAeE309MpdI